ANALISIS PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, LINGKUNGAN KERJA, DAN KOMUNIKASI ORGANISASI TERHADAP KOMITMEN PEGAWAI - -, Samiadji - (Magister Manajemen Universitas Wisnuwardhana, 2016)
Abstract. The organization is a forum that allows someone to get the results or the purpose that were previously not achievable individually or in groups. Thus, the organization is a group of individuals who form cooperation in order to achieve certain goals. Department of Revenue, Finance and Asset Management is to have a strategic role as a coordinator in addition to regional income ,and technical supervisors income areas as well as explore potential sources of local revenue, which is no less important as well as the Regional Treasurer (BUD) is therefore in an effort to increase services to society, Malang Regency Government in the implementation of regional autonomy requires no small amount of funding that officials at DPPKA required to be able to carry out the duties in accordance with the duties of which to increase revenue in an optimal and orderly in its management. The purpose of the study to determine the effect with simultaneously, partial and the most dominant influence of democratic leadership style, work environment and organizational communications to employee commitment DPPKA Malang. The results showed simultaneously and partial variables of democratic leadership style, work environment and employee commitment affect organizational communication DPPKA Malang. While the variables that have the most dominant effect is the working environment, as indicated by the large beta value beta variable between democratic leadership style and organizational communication. Keywords: Democratic leadership style, the working environment, organizational communication, employee commitment